Comparison of Aspergillus-specific antibody cut-offs for the diagnosis of aspergillosis - Hsiao, Chien-Wen; Yen, Tsai-Hung; Wu, Yen-Ching; Chen, Jun-Peng; Chen, Yun-Yu; Huang, Wen-Nan; Chen, Yi-Hsing; Chen, Yi-Ming (Frontiers in Microbiology, 2022)
Background Aspergillus diseases are frequently encountered in patients who are immunocompromised. Without a prompt diagnosis, the clinical consequences may be lethal. Aspergillus-specific antibodies have been widely used to facilitate the diagnosis of Aspergillus diseases. To date, universally standardized cut-off values have not been established. This study aimed to investigate the cut-off values of Aspergillus-specific antibodies and perform a narrative review to depict the geographic differences in the Taiwanese population. Methods From June 2018 to September 2021, we retrospectively enrolled 118 healthy controls and 128 patients with invasive aspergillosis (IA), chronic pulmonary aspergillosis (CPA), and allergic bronchopulmonary aspergillosis (ABPA), who were tested for Aspergillus fumigatus and Aspergillus niger-specific IgG and IgE using ImmunoCAP. Optimal cut-offs and association were determined using receiver operating characteristic curve (ROC) analysis. Results We found that patients with CPA had the highest A. fumigatus-specific IgG levels while patients with ABPA had the highest A. fumigatus-specific IgE, and A. niger-specific IgG and IgE levels. In patients with CPA and ABPA, the optimal cut-offs of A. fumigatus-specific IgG and A. niger-specific IgG levels were 41.6 mgA/l, 40.8 mgA/l, 38.1 mgA/l, and 69.9 mgA/l, respectively. Geographic differences in the cut-off values of A. fumigatus-specific IgG were also noted. Specifically, the levels were higher in regions with higher latitude. Conclusion We identified the optimal cut-offs of Aspergillus-specific antibodies to facilitate a precise diagnosis of aspergillosis. The observed geographic differences of the antibody levels suggest that a country-specific reference is needed to facilitate a prompt and accurate diagnosis of aspergillosis.